2020
DOI: 10.5194/hess-24-4831-2020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing global water mass transfers from continents to oceans over the period 1948–2016

Abstract: Abstract. Ocean mass and thus sea level is significantly affected by water storage on the continents. However, assessing the net contribution of continental water storage change to ocean mass change remains a challenge. We present an integrated version of the WaterGAP global hydrological model that is able to consistently simulate total water storage anomalies (TWSAs) over the global continental area (except Greenland and Antarctica) by integrating the output from the global glacier model of Marzeion et al. (2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…Comprehensive insights into the model sensitivity to choices of irrigation water use assumptions and climate input data were acquired, enabling a first uncertainty estimation. The good fit of simulated monthly total water storage anomaly (sum of land water storage and glacier storage) to GRACE-derived estimates, in particular regarding seasonality and de-seasonalised long-term variability, enhanced the confidence in the simulated land water contributions (Cáceres et al, 2020).…”
Section: Advances On Data Products On Individual Budget Elementsmentioning
confidence: 79%
See 1 more Smart Citation
“…Comprehensive insights into the model sensitivity to choices of irrigation water use assumptions and climate input data were acquired, enabling a first uncertainty estimation. The good fit of simulated monthly total water storage anomaly (sum of land water storage and glacier storage) to GRACE-derived estimates, in particular regarding seasonality and de-seasonalised long-term variability, enhanced the confidence in the simulated land water contributions (Cáceres et al, 2020).…”
Section: Advances On Data Products On Individual Budget Elementsmentioning
confidence: 79%
“…A comparison of the monthly time series of total water and ice storage anomaly (CMC) over the continents (except Greenland and Antarctica) as derived from GRACE and from the non-standard WaterGAP version with glacier integration showed a very good fit, with a modelling efficiency of 0.87 (Cáceres et al, 2020). The GRACE trend during 2003-2016, however, was 26% weaker than the trend from the non-standard WaterGAP version.…”
Section: Methods and Productmentioning
confidence: 97%
“…For the AIS contribution, the new time series of Antarctica mass change from satellite radar altimetry is the result of an improved processing chain and a better characterisation of uncertainties. With a timeevolving ice and snow density mask and a new method for interpolating surface elevation change in areas located beyond the latitudinal limit of satellite radar altimeters and in between satellite tracks, we (sum of land water storage and glacier storage) to GRACE-derived estimates, in particular regarding seasonality and de-seasonalised long-term variability, enhanced the confidence in the simulated land water contributions (Cáceres et al, 2020).…”
Section: Advances On Data Products On Individual Budget Elementsmentioning
confidence: 99%
“…The single exception from this agreement applies to the LWS contribution. While SROCC reports a However, a new GRACE-based assessment of continental mass change (Cáceres et al, 2020, updated by Gutknecht et al, 2020cf. Sect.…”
Section: Budget Closure and Uncertaintiesmentioning
confidence: 99%
“…The authors declare that they have no conflict of interest. S3 -S7 S8 -S13 S26-S28 S40-S45 Moore and Clarke,1981 / Rsat / f(gw) Beven and Kirkby,1979 (Schewe et al, 2019;Hock, 2018, Zekollari et al, 2019;Cáceres et al, 2020); c. couple the climate, lands use, hydrology, and human components including their feedbacks and interactions (Nazemi &Wheater, 2015;Pokhrel et al, 2016;Wada et al, 2017;Thiery et al, 2017;; d. land-use dynamics scheme (Sood and Smakhtin, 2015) Measurements and data (Blöschl et al, 2019) Challenges of simulating terrestrial water cycle on the global scale, identified through the present study 16. How can we use innovative technologies to measure surface and subsurface properties, states, and fluxes at a range of spatial and temporal scales?…”
Section: Supplementmentioning
confidence: 99%